Research on methods of optimizing Flutter applications rendering using a linear regression model - Koba, Y.; Nazarov, O.; Nazarova, N. (ХНУРЕ, 2024)
The research focuses on optimizing the rendering performance of Flutter applications using a linear regression model. The objective is to analyze and compare various rendering optimization techniques by constructing regression equations that model their impact on performance. The study involves identifying critical factors influencing rendering efficiency, applying optimization methods, and using the regression model to evaluate their effectiveness. This approach provides insights into improving UI flow rendering in Flutter applications, contributing to enhanced performance and user experience. Дослідження на оптимізації продуктивності візуалізації програм Flutter за допомогою моделі лінійної регресії. Мета полягає в тому, щоб проаналізувати та порівняти різні методи оптимізації візуалізації шляхом побудови рівнянь регресії, які моделюють їхній вплив на продуктивність. Дослідження передбачає виявлення критичних факторів, що впливають на ефективність рендерингу, застосування методів оптимізації та використання регресійної моделі для оцінки їх ефективності. Цей підхід дає змогу зрозуміти, як покращити візуалізацію потоку інтерфейсу користувача в програмах Flutter, сприяючи підвищенню продуктивності та взаємодії з користувачем.
Keywords: crossplatform; linear regression; mobile apps; rendering; кросплатформа; лінійна регресія; мобільні програми; рендеринг